Hubungan Kadar Glukosa dalam Darah dengan Kadar Kolesterol - Margareta Haiti; Lidwma Septie Christyawardani (Jurnal Keperawatan Silampari, 2023)
This study aims to determine the relationship between glucose levels and cholesterol levels in the blood. The method in this research is an observational study with an analytic study design. The results of this study obtained that glucose levels had an average value of 89.76 mg/dl and cholesterol levels had an average value of 215.92 mg/dl. The analysis of cholesterol levels with glucose in the blood obtained a deal of p=0.646. In conclusion, there is no relationship between blood cholesterol and blood glucose levels. Keywords: Glucose Levels, Cholesterol